English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

y varies jointly with the cube of x and the square of z and inversely with the square of the sum of x and z if y = 72 when x= 2 and z=3 , then find the value of y when x= -1 and z=5.....thx...... I am very lost plz explain all work and answers in detail thx

2007-01-29 15:14:43 · 2 answers · asked by Anthony V 1 in Science & Mathematics Mathematics

2 answers

There must be a proportionality constant; call it k. Then we have y = k x^3 z"2 /(x+z)^2. If y = 72 when ..., we can evaluate k: 72 = k 2*3 3^2 /(2 + 3)^2, so k = 72(25)/72, or 25. The rest is obvious.

2007-01-29 15:30:12 · answer #1 · answered by Anonymous · 0 0

Just a quick guess off the top of my head would be that the problem would be set up like this y-(x+z)^2=(x^3)*(y^2)-(x+z)^2

That would make y = -25

2007-01-29 15:26:33 · answer #2 · answered by Kimmy D 1 · 0 0

fedest.com, questions and answers